First year students' satisfaction towards user education program provided by PTAR Puncak Perdana, UiTM Malaysia / Akbar Malek and Heilda Nor Zairudin - Malek, Akbar; Nor Zairudin, Heilda (Faculty of Information Management, 2010)
This academic project discusses about first year students' satisfaction towards user education program that is provided by PTAR Puncak Perdana, UiTM Malaysia. This research determine outcome and end result about the user education program that provided by PTAR Puncak Perdana. In this research, through expert review, the researchers discussed about the delivery methods' and content that should be done at PTAR Puncak Perdana to make sure first year students' satisfaction towards user education program. This is a survey study which was designed to investigate the first year students' satisfaction towards user education program provided by PTAR Puncak Perdana, UiTM. Hundred (100) first year students of Faculty of Information Management were selected as respondents. The researchers also generate the data collected by using SPSS to get findings. As conclusion, the user education program that is provided by PTAR Puncak Perdana is successful because the respondents give positive comments or views by responding to the questionnaire provided by the researchers.